Analisis Pendekatan Struktural Pada Puisi Berjudul “SILHUET” Karya Taufiq Ismail - Wayan Tiadilona; Munaris Munaris; Heru Prasetyo (Universitas Palangka Raya, 2023)
Poetry is one of the literary genres written in a beautiful and rhythmic language, using words full of meaning and emotions. The purpose of this research is to analyze Taufiq Ismail's poem